Major adverse cardiovascular events in survivors of immune‐mediated thrombotic thrombocytopenic purpura. Issue 12 (15th September 2021) - Brodsky, Max A.; Sukumar, Senthil; Selvakumar, Sruthi; Yanek, Lisa; Hussain, Sarah; Mazepa, Marshall A.; Braunstein, Evan M.; Moliterno, Alison R.; Kickler, Thomas S.; Brodsky, Robert A.; Cataland, Spero R.; Chaturvedi, Shruti
Abstract: Cardiovascular disease is a leading cause of death in survivors of immune‐mediated thrombotic thrombocytopenic purpura (iTTP), but the epidemiology of major adverse cardiovascular events (MACE) in iTTP survivors is unknown. We evaluated the prevalence and risk factors for MACE, defined as the composite of non‐fatal or fatal myocardial infarction (MI), stroke, and cardiac revascularization, during clinical remission in two large iTTP cohorts (Johns Hopkins University and Ohio State University). Of 181 patients followed for ≥ 3 months after recovery from acute iTTP, 28.6% had a MACE event over a median follow up of 7.6 years. Stroke was the most common type of MACE (18.2%), followed by non‐fatal MI (6.6%), cardiac revascularization (4.9%) and fatal MI (0.6%). Compared to the general United States population, iTTP survivors were younger at first stroke in remission (males [56.5 years vs. 68.6 years, p  = 0.031], females [49.7 years vs. 72.9 years, p  <  0.001]) or MI in remission (males [56.5 years vs. 65.6 years, p  <  0.001] and females [53.1 years vs. 72.0 years, p  < 0.001]). Age (HR 1.03 [95% CI 1.002–1.054]), race (Black/Other vs. White) (HR 2.32 [95% CI 1.12–4.82]), and diabetes mellitus (HR 2.37 [95% CI 1.09–0.03]) were associated with MACE in a Cox regression model also adjusted for sex, hypertension, obesity, hyperlipidemia, chronic kidney disease, atrial fibrillation, autoimmune disease, and relapsing iTTP. Remission ADAMTS13 activity was not significantly associated with MACE. In conclusion, iTTP survivors experience high rates of MACE and may benefit from aggressively screening for and managing cardiovascular risk factors.